Automated symptom and treatment side effect monitoring for improved quality of life among adults with diabetic peripheral neuropathy in primary care: a pragmatic, cluster, randomized, controlled trial. Issue 1 (7th November 2018) - Adams, A. S.; Schmittdiel, J. A.; Altschuler, A.; Bayliss, E. A.; Neugebauer, R.; Ma, L.; Dyer, W.; Clark, J.; Cook, B.; Willyoung, D.; Jaffe, M.; Young, J. D.; et al.
Abstract: Aims: To evaluate the effectiveness of automated symptom and side effect monitoring on quality of life among individuals with symptomatic diabetic peripheral neuropathy. Methods: We conducted a pragmatic, cluster randomized controlled trial (July 2014 to July 2016) within a large healthcare system. We randomized 1834 primary care physicians and prospectively recruited from their lists 1270 individuals with neuropathy who were newly prescribed medications for their symptoms. Intervention participants received automated telephone‐based symptom and side effect monitoring with physician feedback over 6 months. The control group received usual care plus three non‐interactive diabetes educational calls. Our primary outcomes were quality of life (EQ‐5D) and select symptoms (e.g. pain) measured 4–8 weeks after starting medication and again 8 months after baseline. Process outcomes included receiving a clinically effective dose and communication between individuals with neuropathy and their primary care provider over 12 months. Interviewers collecting outcome data were blinded to intervention assignment. Results: Some 1252 participants completed the baseline measures [mean age (sd ): 67 (11.7), 53% female, 57% white, 8% Asian, 13% black, 20% Hispanic]. In total, 1179 participants (93%) completed follow‐up (619 control, 560 intervention). Quality of life scores (intervention: 0.658 ± 0.094; control: 0.653 ± 0.092) and symptom severity were similar at baseline. The intervention had no effect on primary [EQ‐5D: −0.002 (95% CI −0.01, 0.01), P = 0.623; pain: 0.295 (−0.75, 1.34), P = 0.579; sleep disruption: 0.342 (−0.18, 0.86), P = 0.196; lower extremity functioning: −0.079 (−1.27, 1.11), P = 0.896; depression: −0.462 (−1.24, 0.32); P = 0.247] or process outcomes. Conclusions: Automated telephone monitoring and feedback alone were not effective at improving quality of life or symptoms for people with symptomatic diabetic peripheral neuropathy. Trial Registration: ClinicalTrials.gov (NCT02056431). What's new?: Frequent communication between individuals with diabetic peripheral neuropathy and primary care providers about symptoms and medication side effects is critical to optimizing medication dosing to treat painful diabetic peripheral neuropathy. Yet, there are considerable barriers to effective communication. This cluster randomized controlled trial found that a brief intervention to automatically monitor person‐reported data on symptoms and side effects, and provide the information to physicians via an electronic health record was not effective in improving the outcomes valued by individuals with neuropathy. Alerts alone are unlikely to change provider behaviour related to treatment intensification. More intensive interventions focused on individual activation or provider education may be more effective in changing prescribing behaviour and improving outcomes.